2011
DOI: 10.1007/s10775-011-9189-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the short form of the career development inventory with an Iranian high school sample

Abstract: A short 33-item form of the Career Development Inventory was validated on a sample of 310 Iranian high school students. Factor analysis indicated that attitude and cognitive subscale items loaded on their respective factors, and that internal reliability coefficients at all levels were satisfactory to good. Support for validity was demonstrated by associations in the expected direction for career decidedness and career decision-making self-efficacy. This short form of the inventory shows promise as a measure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…These values of reliability are lower than .70, which is traditionally regarded as the cutoff for acceptability (Nunnally & Bernstein, 1994). However, the values are comparable with those obtained in other studies (e.g., Cronbach's α = .66; Sadeghi, Bahrami, Ahmadi, & Creed, 2011). A further limitation is that the collected demographic data were limited to gender, age, and attended school.…”
Section: Strengths Limitations and Practice Implicationssupporting
confidence: 86%
See 1 more Smart Citation
“…These values of reliability are lower than .70, which is traditionally regarded as the cutoff for acceptability (Nunnally & Bernstein, 1994). However, the values are comparable with those obtained in other studies (e.g., Cronbach's α = .66; Sadeghi, Bahrami, Ahmadi, & Creed, 2011). A further limitation is that the collected demographic data were limited to gender, age, and attended school.…”
Section: Strengths Limitations and Practice Implicationssupporting
confidence: 86%
“…This choice was due to the lack of instruments designed to assess outcome variables in career guidance and counseling (Bernes, Bardick, & Orr, 2007). However, the values are comparable with those obtained in other studies (e.g., Cronbach's α = .66; Sadeghi, Bahrami, Ahmadi, & Creed, 2011). Specifically, the Career Exploration subscale had minimally acceptable Cronbach's alphas of .53 (Time 1) and .64 (Time 2).…”
Section: Strengths Limitations and Practice Implicationsmentioning
confidence: 52%
“…Specifically, it assesses decisiveness-the extent of firmness about one's preferred orientation toward career, preparation-the degree of understanding and planning of one's career choice, independence-the degree of one's independent career decision-making, goal orientation-the degree to which one prefers self-improvement through one's career, and confidence-the degree of one's faith and sureness in the chosen career. Prior studies suggest that individuals with high career maturity, compared to those of low career maturity, are likely to have high levels of career certainty and decision-making self-efficacy (e.g., Sadeghi, Baghban, Bahrami, Ahmadi, & Creed, 2011), succeed in further education, and report subjective career success (e.g., Hirschi, 2010;Patton, Creed, & Muller, 2002). Given this positive side of career maturity, much attention has been paid to factors accounting for career maturity.…”
Section: Introductionmentioning
confidence: 99%
“…The educational system in Iran is based on a large amount of content, intensive training with an emphasis on theoretical learning, and successive examinations. This system affects students’ satisfaction, self-efficacy, and academic performance (Sadeghi, Baghban, Bahrami, Ahmadi, & Creed, 2011; Sadeghi, Baghban, Bahrami, Ahmadi, & Sadeghi, 2012). It is reported that Iranian university students have low motivation (Sadeghi & Rabiei, 2016) and low self-efficacy (Sadeghi, 2016).…”
mentioning
confidence: 99%